Cataloguing of government publications - Suja', Balqis (2007)
This is a one-and-a-half hour presentation and a two-and-a-half hour hands-on cataloguing the official publications. Participants were introduced to the definition of official publications, the types of the documents, awareness on multiformats of present days government publications and its arrangement in the catalogue, corporate headings and its authority control, the Skim Pengkelasan Terbitan Kerajaan Malaysia, and the non-Malaysian official publications. The later part of the training was exposure on the cataloguing operations and shelflisting of the materials at IIUM Library, supplemented with brief hands on.